Characterised of the mechanical and electrical behavior of electrostatic power generator - Lv, Xing. (2011)
The increasing demand in energy consumption and widespread application of remote wireless sensor networks boost the research in renewable energy sources for replacement of conventional disposable batteries. As a universally present energy, vibration energy is of great interest for investigation. As the electrode of a capacitor moves following external loads, the capacitance varies and inductive current is formed. In this project, the study on the design of the supporting flexure for the movable component of micro vibration harvesters and simulation using ANSYS are carried out. Discussion about the effect of the design parameters on spring stiffness is conducted. Testing on capacitance change in standstill condition while varying the overlapping area and gap of capacitors was also carried out.